HUMAN CONCEPTS IN THE QURAN AND ITS APPLICATIONS IN INTEGRATED ISLAMIC ELEMENTARY SCHOOL (SDIT) AL-MADINAH PEKANBARU (INSAN, INS, BASYAR, BANU ADAM) - Siregar, Kardina Engelina (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The aim of education for Muslims is to increase piety to Allah Subhanahu wa Ta'ala. This is a supporter of the realization of Integrated Islamic education which is able to combine general knowledge and religious knowledge. One of the tasks of the teacher as an educator at the Integrated Islamic School is to educate students to understand the concept of humans as servants of Allah, to understand all the potentials and weaknesses possessed by humans. This human concept education must have a clear foundation so that the main goal in education, namely increasing piety to Allah Subhanahu wa Ta'ala can be realized. This paper aims to discuss human concept material in the Qur'an in terms of (insan, ins, basyar, banu adam) and its implications for the Integrated Islamic Elementary School (SDIT) Al-Madinah Pekanbaru. The research method used is qualitative research. The qualitative approach used is a phenomenological approach. There are two sources of research data, namely literature review and field research. In the field research, interviews were conducted with school principals and teachers who teach Islamic religious education. Data collection technique used is interview. The research questions are prepared based on thematic interpretations of human beings, ins, naas, basyar, banu adam. After the data is collected, then the data is analyzed using a qualitative descriptive analysis technique, namely by describing the data as it is. From the results of the study it can be concluded that teachers must try to apply understanding of human concepts according to the Koran with the right method which is very important to apply to students. This is in order to understand who he is as a servant of God and as a social being.